Automated steam engine technology for eco-printing batik: Empowering community economies - Shazana Dhiya Ayuni; Alfarid Hendro Yuwono; Akhmad Mulyadi; Syamsudduha Syahrorini; Agus Hayatal Falah (Community Empowerment, 2024)
This community service initiative aimed to empower batik artisans in Pamekasan and Pacet villages by enhancing their economic prospects. The team disseminated automated steam engine technology for eco-printing batik to expedite the production process. The activities involved training in various aspects, including eco-printing, automated steam engine usage, cost calculation, and product branding. The outcomes revealed the unique appeal of eco-printing batik motifs, which have become a trend among environmental enthusiasts and fashionistas. The technology dissemination also streamlined the production process, allowing for 18 rolls of fabric to be steamed simultaneously, ultimately reducing production costs. Additionally, batik artisans gained the ability to determine product prices and market their creations through e-commerce platforms.